MEQSA-OLSRv2: A Multicriteria-Based Hybrid Multipath Protocol for Energy-Efficient and QoS-Aware Data Routing in MANET-WSN Convergence Scenarios of IoT - Jabbar, Waheb A.; Saad, Wasan Kadhim; Mahamod, Ismail (IEEE, 2018)
Convergence of typical wireless networks [mobile ad hoc network (MANET) and wire-less sensor network (WSN)] is paving the way toward brand-new cooperative platforms for Internet of Things (IoT) communications. The IoT enables the global connectivity of a wide variety of heterogeneous objects in accordance with their battery capacity, processing capabilities, and mobility to serve people in a collaborative manner automatically and intelligently. In such ubiquitous smart environments, efficient and effective data routing among IoT devices represent a real challenge due to nodes heterogeneity. Thus, this paper proposes a hybrid multipath energy and quality of service (QoS)-aware optimized link state routing protocol version 2 (MEQSA-OLSRv2), which is developed to cope with the challenges presented by limited energy resources, mobility of nodes, and traffic congestion during data transmission in the MANET-WSN convergence scenarios of IoT networks. This protocol uses a node rank according to multicriteria node rank metric (MCNR). This MCNR aggregates multiple parameters related to energy and QoS into a comprehensive metric to dramatically reduce the complexity of multiple constrained considerations and avoid the control overhead caused by separately broadcasting multiple parameters. These metrics are the node’s lifetime, residual battery energy, node’s idle time, node’s speed, and queue length. The MCNR metric is utilized by a new link quality assessment function for multiple-route computation. It is also adopted to select a multipoint relay (MPR) set of nodes by using an energy and QoS-aware MPR selection mechanism for flooding topological information. The simultaneous consideration of energy and QoS parameters can benefit the tradeoff between QoS and energy awareness. The performance of the MEQSA-OLSRv2 is evaluated through EXata-based simulations, and its effectiveness is validated by comparing it with the conventional routing protocols. The MEQSA-OLSRv2 is found to outperform existing schemes even in heavy traffic load and high-mobility scenarios. Furthermore, the MEQSA-OLSRv2 considerably enhances QoS, reduces energy consumption, and decreases the energy cost per packet